Self-Esteem and Dietary Behavior in Adolescent Women - Assifa, Amalia; Setiyani, Ratna Yunita (Journal of Health Sciences and Medical Development, 2023)
Adolescence is a period that usually occurs and experiences life upheaval caused by various physical, psychological and social changes. One of the main problems teenagers face, especially female adolescents, is their weight and appearance. The study aims to determine the correlation between dietary behaviour and self-esteem in adolescents. This study employed a quantitative methodology with a correlation approach. The respondents in this study were female adolescents in Yogyakarta who were overweight and desired to lose weight. The number of respondents was 105 people. The sampling technique used purposive sampling. The data collection used scale filling, while the data analysis used Pearson Product Moment correlation. The results revealed that 26 female adolescents had a high level of self-esteem with a percentage of 25%, 79 female adolescents had a moderate level of self-esteem with a percentage of 75%, and no female adolescents had a high level of self-esteem. There is a significant correlation between self-esteem and dietary behaviour in female adolescents in Yogyakarta, with a correlation coefficient of 0.400 with a positive direction. Thus, it can be assumed that the higher the self-esteem, the higher the dietary behaviour of female adolescents in Yogyakarta. Likewise, the lower the level of self-esteem, the lower the dietary behaviour of female adolescents in Yogyakarta.